Effect of Trade Liberalization on Per Capita Income in Nigeria - Onyendi, Hilary Uchenna (Social Science Research, 2022)
This study investigated the effect of trade liberalization on per capita income in Nigeria from 1972 to 2020. Contributions of trade liberalization to gross domestic product have been robust as evidenced in the literature. Yet this appears not to have any corresponding impact on the people as poverty, unemployment, low income, inequitable income distribution remain prevalent. This calls for further investigation. This study adopted secondary sources for data collection. The sources of data were from the Central Bank of Nigeria (CBN) Statistical Bulletin of various issues. The econometric tools used in this study include the unit root test, Johansen co integration test and the Granger causality test. This study revealed that trade liberalization has negative effect on per capita income in Nigeria within the period under review. This implies that the average income of the citizen is not explained by trade liberalization Nigeria. In general the findings of study further established that despite the rising contribution of trade liberalization to the gross domestic product in Nigeria, the citizens have not felt the impact as hunger, unemployment and poverty is prevalent in the country. The recommendations include that the government should implement external trade policies that will foster and engender trade liberalization such as improving on the easy- of- doing- business procedures. Also there is need to put in place income policies that will stimulate income redistribution among the citizens.